Antecedent and mediators of life satisfaction among undergraduates in the Klang Valley, Malaysia - Ramachandran, Kunnasunthary (2019)
Higher education students, especially undergraduates who are in a transitional social period, face many confusions and challenges in their learning environment. Indeed, life stresses that undergraduates encounter can be overwhelming and can have a serious impact on their level of life satisfaction. Life satisfaction is considered to be a central aspect of students’ quality of life. It is the ultimate goal, and students strive to achieve this goal throughout their learning life. Therefore, this research focused on investigating the factors which can be used as predictors of life satisfaction among undergraduate students in Klang Valley universities. This research aimed to identify the relationship between emotional intelligence and life satisfaction, mediated by attachment relationship, immediacy behaviour, interpersonal needs and interpersonal attraction. This study applied Emotional Intelligence Model and PERMA Model as a theoretical framework. About 600 Malaysian undergraduate students from Klang Valley participated as respondent and this study chosen using a multistage cluster sampling techniques. Data were gathered through survey questionnaire and analysed using SPSS. Two types of data analyses were conducted. First, the descriptive analysis is to identify the levels of all the related variables and second the inferential analysis is performed using Chi-Square test, Pearson Correlation test, Independent T-test, Binary Logistic Regression and Hayes Bootstrapping Mediation Analysis to test nine hypothesis drawn from the research model. The findings indicate that student with higher life satisfaction had a high level of emotional intelligence, attachment relationship, immediacy behaviour, interpersonal attraction and interpersonal needs. Furthermore, the logistic regression analysis indicated that attachment relationship of peers and immediacy behaviour of lecturers are strongest predictors which associated with life satisfaction among undergraduates. The bootstrapping analysis showed immediacy behaviour, interpersonal needs and attachment relationship as the significant mediators between emotional intelligence and life satisfaction. Finally, this study confirmed all the predictors jointly explained 13% of the variance life satisfaction. Based on these findings, the implication and recommendation for future investigation to the current theoretical framework and empirical findings that social variables such as immediacy behaviour, attachment relationship and international needs more influenced undergraduates’ life satisfaction compared emotional intelligence in this research context.